Replacement of the V3 Domain in the Surface Subunit of the Feline Immunodeficiency Virus Envelope Glycoprotein with the Equivalent Region of a T Cell-Tropic Human Immunodeficiency Virus Type 1 Results in a Chimeric Surface Protein That Efficiently Binds to CXCR4 - Gonzalez, Silvia Adriana (2014)
Feline immunodeficiency virus (FIV) and the T cell-tropic strains of human immunodeficiency virus type 1 (HIV-1) share the use of the chemokine receptor CXCR4 for cell entry. To study this process further we developed a cell surface binding assay based on the expression of a soluble version of the FIV SU C-terminally tagged with the influenza virus hemagglutinin epitope (HA). The specificity of the assay was demonstrated by the following evidence: (1) the SU-HA protein bound to HeLa cells that express CXCR4 but not to MDCK cells that lack this chemokine receptor; and (2) binding of the SU-HA to HeLa cells was blocked by incubation with the CXCR4 antagonist AMD3100 as well as with the anti-CXCR4 monoclonal antibody (MAb) 12G5. Deletion of the V3 region from the FIV SU glycoprotein abolished its ability to bind CXCR4-expressing cells. Remarkably, substitution of the V3 domain of the FIV SU by the equivalent region of the HIV-1 NL4-3 isolate resulted in efficient cell surface binding of the chimeric SU protein to CXCR4. Moreover, transfection of MDCK cells with a plasmid encoding human CXCR4 allowed the association of the chimeric SU-HA glycoprotein to the transfected cells. Interestingly, while cell binding of the chimeric FIV-HIV SU was inhibited by an anti-HIV-1 V3 MAb, its association with CXCR4 was found to be resistant to AMD3100. Of note, the chimeric FIV-HIV Env glycoprotein was capable of promoting CXCR4-dependent cell-to-cell fusion.